Efficient visible driven photocatalyst, silver phosphate: performance, understanding and perspective. (23rd July 2015) - Martin, David James; Liu, Guigao; Moniz, Savio J. A.; Bi, Yingpu; Beale, Andrew M.; Ye, Jinhua; Tang, Junwang
Abstract : Photocatalysis is a promising technology that can contribute to renewable energy production from water and water purification. Abstract : Photocatalysis is a promising technology that can contribute to renewable energy production from water and water purification. In order to further develop the field and meet industrial requirements, it is imperative to focus on advancing high efficiency visible light photocatalysts, such as silver phosphate (Ag3 PO4 ). This review aims to highlight the recent progress made in the field, focusing on oxygen production from water, and organic contaminant decomposition using Ag3 PO4 . The most important advances are discussed and explained in detail, including semiconductor–semiconductor junctions, metal–semiconductor junctions, exposing facet control, and fundamental understanding using advanced spectroscopies and computational chemistry. The review then concludes by critically summarising both findings and current perspectives, and ultimately how the field might best advance in the near future.